"Resuscitate and Push": End-of-Life Care Experiences of Healthcare Staff in the Emergency Department – A Hermeneutic Phenomenological Study. Issue 4 (October 2022) - Bayuo, Jonathan; Anago, Emmanuel Kwadwo; Agyei, Frank Bediako; Salifu, Yakubu; Kyei Baffour, Prince; Atta Poku, Collins
Objective: Care in the emergency department focuses significantly on delivering lifesaving/ life-sustaining clinical actions, often with limited attention to health-related suffering even at the end-of-life. How healthcare staff experience and navigate through the end-of-life phase remains minimally explored. Thus, this study aimed to uncover the lived experiences of emergency department staff at the end-of-life.Methods: van Manen's hermeneutic phenomenological approach was used. Nineteen healthcare staff were purposively recruited and interviewed. Interviews were audio-taped, transcribed verbatim, and thematic categories formulated. The existential lifeworld themes (corporeality, relationality, spatiality, and temporality) were used as heuristic guides for reflecting and organizing the lived experiences of participants.Results: The overarching category, ' resuscitate and push', was captured as corporeality (resisting death and dying); relationality (connectedness to the body of the patient; and lacking support for family and self); spatiality (navigating through a liminal space and lack of privacy for patients); and temporality (having limited to no time for end-of-life care and grieving). The end-of-life space was unpleasant. Although participants experienced helplessness and feelings of failure, support systems to help them to navigate through these emotions were lacking. Grief was experienced covertly and concealed by the entry of a new patient.Conclusion: End-of-life in the emergency department is poorly defined. In addition to shifting from the traditional emergency care model to support the streamlining of palliative care in the department, staff will require support with navigating through the liminal space, managing their grief, and developing a better working relationship with patients/ families.